Outcome of diaphyseal pediatric forearm fractures following non-surgical treatment in a Level I Trauma Center: Outcome of Diaphyseal Pediatric Forearm Fractures Following Non-Surgical Treatment in a Level I Trauma Center - Alrashedan, Bander S; Jawadi, Ayman H.; Alsayegh, Samir Omar; Alshugair, Ibrahim F.; Alblaihi, Mohammed; Jawadi, Tariq A.; Hassan, Anas Ahmed; Alnasser, Abdulrahman Mohammed; Aldosari, Nawaf Bakhit; Aldakhail, Mishary Abdulaziz (International Journal of Health Sciences, 2018)
Objectives: Pediatric diaphyseal forearm fractures are common injuries of childhood. Conservative modality of treatments is usually preferred when they are possible. We identified factors that may affect closed reduction success or lead to redisplacement in forearm diaphyseal fractures in children. Methods: This was a retrospective study from a level I trauma center on patients up to 18 years of age who presented with forearm diaphyseal fractures from January 1, 2007, to December 31, 2015. Cases were obtained from medical records. Data were collected and confirmed by plain films and medical files. Results: We included 145 patients in this study. The majority (86.2%) were boys. Around 29% of trials of closed reduction failed, and the patients were subsequently treated surgically. Following trials of closed reduction, 82.4% of both bone cases were successfully reduced compared to 42.9% of radius shaft cases (P = 0.006). Redisplacement following non-surgical treatment in the first follow-up was found in 32% of both bone cases and 13.3% of radial shaft cases. All Galeazzi cases that were successfully treated with closed reduction presented with no redisplacement on follow-up. Conclusion: Immediate surgical management might be considered in older children, especially above 12 years of age since they have a higher failure rate of closed reduction than younger ones. Fracture site should be taken into account when following pediatric diaphyseal forearm fractures following conservative treatments as cases with both bone involvement have a high success rate of closed reduction and considerably high rate of redisplacement compared to others.